Effect of colorlessness condition on phase transition from Hadronic Gas to partonic plasma - Abdul Raheem Ahmed, Mohamed Abdul Malek; Cherif, S.; Ladrem, M.; Zainuddin, Hishamuddin; Mohd Shah, Nurisya (Malaysian Institute of Physics, 2018)
One of the most important phase transition in physics is the Deconfinement Phase Transition in thermal Quantum ChromoDynamics. Due to the confinement property, we study the effect of colorlessness condition during the Deconfinement Phase Transition from a Hadronic Gas to a Quark-Gluon Plasma. We investigate the behavior of some thermodynamical quantities of the system such as the energy density and the pressure, the colorlessness condition and without colorlessness.